RANCANG BANGUN INVERTER 1 FASA DENGAN TEKNIK MODULASI THIRD HARMONIC INJECTION PULSE WIDTH MODULATION UNTUK PANEL SURYA 1 KWP - Firman Hidayat Jati Pamungkas; Bambang Sujanarko; Moch Gozali (Jurnal Arus Elektro Indonesia, 2020)
Indonesia is a tropical country, means that Indonesia gets more sun exposure than other countries. Therefore, Indonesia has the potential to develop Renewable Energy, especially solar panels. Solar panels can be used in homes for small scale, as well as on large scale such as power plants. However, electricity generated from solar panels cannot be directly used for some household appliances, because electricity produced is direct current (DC) electricity. So we need a device that can convert DC electricity into AC electricity (Alternating Current) called an inverter. A good inverter is one that has a THD (Third Harmonic Distortion) rating of no more than 5%. High THD can damage electronic equipment. Therefore, this study uses the THIPWM modulation method that is able to reduce THD.